2021
DOI: 10.21107/agrointek.v15i3.10149
|View full text |Cite
|
Sign up to set email alerts
|

Quality Analysis of "Kosmos" TKKS Compose Using Selulotic Microorganism

Abstract: This study aimed to determine the comparison of the chemical composition of oil oil palm empty friut bunches (TKKS) compost using cellulolytic microorganisms and TKKS compost. This research is a descriptive study that describes the chemical composition of compost with cellulolytic microorganisms. The treatments used in this study were the differences in the ratio of TKKS and cow dung KM1 (100: 0), KM2 (90:10), KM3 (80:20), KM4 (70:30), KM5 (60:40) and KM6 ( 50:50). This study's results were the selected treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The content of slow release potassium fertilizer is C-Organic 20.21%, C/N Ratio 24.57%, N 0.82%, P2O5 13.10%, K2O 20.93%. Research by Pramana et al (2021) showed that fertilizer from empty fruit bunches had N content of 0.73%, C-Organic 9.28%, C/N ratio 12.29%, P 0.42%, K 3.99%, while the content of EFB only. N 6.28%, C-Organic 14.19%, C/N ratio 2.26%, P 1.88%, K 2.51% and Mg 1.61%…”
Section: Introductionmentioning
confidence: 99%
“…The content of slow release potassium fertilizer is C-Organic 20.21%, C/N Ratio 24.57%, N 0.82%, P2O5 13.10%, K2O 20.93%. Research by Pramana et al (2021) showed that fertilizer from empty fruit bunches had N content of 0.73%, C-Organic 9.28%, C/N ratio 12.29%, P 0.42%, K 3.99%, while the content of EFB only. N 6.28%, C-Organic 14.19%, C/N ratio 2.26%, P 1.88%, K 2.51% and Mg 1.61%…”
Section: Introductionmentioning
confidence: 99%